Muslim and non-muslim differences in female autonomy and fertily : Evidence from four asian countries - Morgan, S. P.; Stash, S.; Smith, H. L.; Mason, K. o.
tbls.
pp. 515-537
Keywords: Fecundidad; Musulmanes; Religion; Autonomía; Mujeres; Natalidad; Genero; India; Malasia; Filipinas; Tailandia; Asia